2017
DOI: 10.1111/wrr.12500
|View full text |Cite
|
Sign up to set email alerts
|

The role of allogenic keratin‐derived dressing in wound healing in a mouse model

Abstract: Keratin is an interesting protein needed for wound healing and tissue recovery. We have recently proposed a new, simple and inexpensive method to obtain fur and hair keratin-derived biomaterials suitable for medical application. The aim of the study was to evaluate the role of the fur keratin-derived protein (FKDP) dressing in the allogenic full-thickness surgical skin wound model. The data obtained using scanning electron microscopy showed that employed processed biomaterial had higher surface porosity compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 35 publications
3
36
0
1
Order By: Relevance
“…However, in control animals, after wound induction, some signs of oozing were observed, although without exceeding 10–15% of the wound total area. Our previous experiments and literature data have showed that keratin biomaterials possess some sorption properties (Konop et al, ). Statistical analysis revealed that applying the dressing significantly accelerated wound healing in the first 8 days after wounding.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, in control animals, after wound induction, some signs of oozing were observed, although without exceeding 10–15% of the wound total area. Our previous experiments and literature data have showed that keratin biomaterials possess some sorption properties (Konop et al, ). Statistical analysis revealed that applying the dressing significantly accelerated wound healing in the first 8 days after wounding.…”
Section: Discussionmentioning
confidence: 94%
“…In our previous study performed on normal mice, macrophages and histiocytes predominated in wounds treated with FKDP dressing. On the other hand, in the control wounds, neutrophils with occasional histiocytes and lymphocytes were continuously present during post‐wounding period (Konop et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only few studies of keratin have discussed about the development of such biomaterial in stem cells and animal models tissue engineering applications (Konop et al, , Konop et al, , Lin, Yang, et al, ). The present study provides systematic in vitro and in vivo investigations of different concentration of keratin scaffolds produced using the freeze‐drying technique.…”
Section: Discussionmentioning
confidence: 99%
“…Keratin has been employed in biomedical utilization, especially for hemostasis and wound healing (Konop et al, 2017;Shavandi, Silva, Bekhit, & Bekhit, 2017;Than et al, 2012). Previous researches indicated that keratin extracted from human hair fibers contains cell adhesion (motifs RGD [Arg-Gly-Asp] and LVD [Leu- Asp-Val], which are also found in extracellular matrix proteins such as fibronectin (Makarem & Humphries, 1991;Marshall, Orwin, & Gillespie, 1991;Yamauchi, Hojo, Yamamoto, & Tanabe, 2003).…”
mentioning
confidence: 99%